The Implementation of Electronic Litigation (e-Litigation) in Efforts to Realize the The Principles of Swift, Simple, and Cost-effective Trials at Semarang District Court: Pelaksanaan Persidangan Elektronik (e-Litigation) dalam Upaya Mewujudkan Asas Persidangan Cepat, Sederhana, Biaya Ringan di Pengadilan Negeri Semarang - Safitri, Anisa Endah Dwi; Latifiani, Dian (Faculty of Law, Universitas Negeri Semarang, 2024)
Innovative solutions are needed to enhance the efficiency and affordability of the trial process. One such solution is e-Litigation, an electronic trial system that utilizes technology to realize the principles of swift, simple, and cost-effective trials. However, its implementation faces challenges such as limited human resources, infrastructure, and administrative processes. The formulation of the research problem is as follows: 1) How is the Implementation of Electronic Litigation (e-Litigation) in Efforts to Realize the Principles of Swift, Simple, and Cost-Effective Trials at Semarang District Court? 2) What are the obstacles and their solutions in the Implementation of Electronic Litigation (e-Litigation) in Efforts to Realize the Principles of Swift, Simple, and Cost-Effective Trials at Semarang District Court? The research approach used is qualitative legal research with an empirical juridical type. Data is obtained through interviews, documentation, and literature review. Data validity is ensured through triangulation by comparing primary data with secondary data. Data analysis is conducted in three stages: data reduction, data display, and conclusion drawing. The research findings explain the implementation of electronic trials at Semarang District Court to realize the principles of swift, simple, and cost-effective trials based on Supreme Court Regulation No. 7 of 2022 on electronic trials to ensure optimal law enforcement by law enforcement officials during the trial process. There are self-reliant individuals in the community who seek legal assistance independently, and if there are obstacles, they can consult through the e-court corner, Legal Aid Institute of Semarang District Court, or use legal representation in seeking justice. The correlation between the principles of swift, simple, and cost-effective trials and the implementation of electronic trials at Semarang District Court can be seen from the maximum trial time limit of 5 months, features allowing parties to access, download, and upload trial-related documents, integration of electronic media for summoning parties, effective archiving systems, efficiency in trial needs, especially accommodation costs, creating transparency, and eradicating brokers and illegal levies. There are several obstacles including Lack of Public Knowledge, which significantly affects the effectiveness of the law, especially if there are technologically inexperienced individuals who tend to resist change and distrust the legal system. The second factor is Lack of Infrastructure (Network Constraints).